Heavy metals quantification on alkaline batteries incineration emissions - Xará, Susana (2011)
Heavy metals emissions associated with municipal solid waste (MSW) incineration is a point of discussion and care due to the known harmful effects of these metals on humans and environment. Batteries are appointed as one of the main contributors for those emissions, particularly for mercury, cadmium, zinc and lead. In this paper, results for heavy metals emissions from alkaline batteries obtained in a laboratorial incinerator are presented. The incineration process took place in a tubular oven where batteries were heated at 1000°C with a constant airflow. Heavy metals on released gas were collected with concentration by absorption on a set of serial bubblers, and, following, quantified by atomic absorption spectroscopy. The results obtained estimate the potential contribution of alkaline batteries to heavy metals emissions in a municipal solid waste incinerator.